2022
DOI: 10.5897/ajar2022.16102
|View full text |Cite
|
Sign up to set email alerts
|

Development and testing of a vertical-spikes shelling machine for bambara groundnuts

Abstract: This paper aim to develop a low-cost Bambara groundnuts sheller that uses vertical spikes as the shelling mechanism. A vertical spike shelling machine was designed, constructed and evaluated. The Bambara groundnut shelling machine consisted of a hopper, shelling system, frame, motor and power transmission system. The Bambara groundnut sheller used a low-cost shelling mechanism of spikes and shaft system, as it has ability to break different sizes of the Bambara groundnut pods. The prototype was tested for shel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
1
0
0
Order By: Relevance
“…There was a strong positive correlation between ρ b , and mc (Table 4). This finding agreed with the study of Nkambule et al (2023) for Bambala groundnut seed which observed an increasing trend in the seed bulk density with increased mc.…”
Section: Resultssupporting
confidence: 93%
“…There was a strong positive correlation between ρ b , and mc (Table 4). This finding agreed with the study of Nkambule et al (2023) for Bambala groundnut seed which observed an increasing trend in the seed bulk density with increased mc.…”
Section: Resultssupporting
confidence: 93%